(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
this article examines the issues of developing pedagogical tact in future educations. Pedagogical tact is an important factor in a teacher’s professional culture, moval character, and effective interaction with children. The article explains the concept of pedagogical tact, its main qualities in future specialists. Additionally, the significance of pedagogical tact in the educational process and its role in the professional training of future educators is highlighted.